Towards the fate of the oscillating false vacuum - Darmé, Luc; Jaeckel, Joerg; Lewicki, Marek (Physical review, 2017)
Motivated by cosmological examples, we study quantum field theoretical tunneling from an initial state where the “classical field,” i.e. the vacuum expectation value of the field operator, is spatially homogeneous but performing a time-dependent oscillation about a local minimum. In particular, we estimate both analytically and numerically the exponential contribution to the tunneling probability. We additionally show that after the tunneling event, the classical field solution—the so-called “bubble”—mediati the phase transition can either grow or collapse. We present a simple analytical criterion to distinguish between the two behaviors.